PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERNUANSA PBI (PROBLEM BASED INSTRUCTION) PADA POKOK BAHASAN TEOREMA PYTHAGORAS UNTUK SISWA KELAS VIII SMP - K, Maharani Gita; Trapsilasiwi, Dinawati; Kristiani, Arika Indah (KadikmA, 2013)
Abstract. PBI (Problem Based Instrustion) is a Learning Model that focused on the students mind set and activity in the learn process. The purpose of the study are to describe the process and result in the Development of Mathematics Learning Materials PBI nuanced of Pythagoras Theorem topic for Eight Grade Junior High School. The development model refers to 4D Thiagarajan models which has 4 steps are define, design, developt, and disseminate.The result of thisresearchare lesson plan, worksheet, student book, evaluation test. From the validationsource and the trial of the learning sets can be concluded that the learning sets had been appropriate with validate, practice, and effective criteria. Key Words: Problem Based Instruction (PBI) Learning Model, 4D Thiagarajan models, Pythagoras theorem.